One-step hydrothermal method to fabricate drag reduction superhydrophobic surface on aluminum foil - Tuo, Yanjing; Chen, Weiping; Zhang, Haifeng; Li, Pujun; Liu, Xiaowei (Applied surface science, 2018)
•Superhydrophobic surface is prepared on aluminum foil by a novel one-step hydrothermal method.•The superhydrophobic surface can reduce the friction resistance between solid-liquid interface.•The superhydrophobic surface also shows self-cleaning and anti-icing properties. Superhydrophobic surface, covered by micro or nano textured layer, can trap and retain air pockets and possesses unique excellent properties. Here we propose a novel one-step hydrothermal method to fabricate superhydrophobic surface on aluminum foil. The film of sheet structure is Al[CF3(CF2)12COO]3, which can provide micro structures and reduce surface energy. The as-prepared surface with high contact angle and low sliding angle has some interesting characteristics. In the test, the powder dirt can be easily removed from the surface and the formation of ice is inhibited on it. The drag reduction ratio of the superhydrophobic surface is about 20–30% at the velocity of 2–5 m/s. We envision this superhydrophobic surface has a great prospect in industrial applications.